1995
DOI: 10.1056/nejm199505253322101
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of the Androgen-Receptor Gene in Metastatic Androgen-Independent Prostate Cancer

Abstract: Most metastatic androgen-independent prostate cancers express high levels of androgen-receptor gene transcripts. Mutations in androgen-receptor genes are not uncommon and may provide a selective growth advantage after androgen ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
689
0
7

Year Published

1997
1997
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,125 publications
(719 citation statements)
references
References 27 publications
23
689
0
7
Order By: Relevance
“…Tumour cells with mutations of the AR gene may enable transactivation of the AR by other steroids than the usual ligand dihydrotestosterone. 2,18 Furthermore, we recently found ampli®cation of the AR gene in about one third of tumours recurring during androgen deprivation. 19 The ®nding in the present study that recurrent tumours with AR ampli®cation were more highly proliferative, and more often aneuploid than their counterparts with no AR ampli®cation supports the signi®cance of AR gene ampli®cation in tumour recurrence and endocrine therapy failure.…”
Section: Discussionmentioning
confidence: 99%
“…Tumour cells with mutations of the AR gene may enable transactivation of the AR by other steroids than the usual ligand dihydrotestosterone. 2,18 Furthermore, we recently found ampli®cation of the AR gene in about one third of tumours recurring during androgen deprivation. 19 The ®nding in the present study that recurrent tumours with AR ampli®cation were more highly proliferative, and more often aneuploid than their counterparts with no AR ampli®cation supports the signi®cance of AR gene ampli®cation in tumour recurrence and endocrine therapy failure.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations have been widely reported in 10-50% of recurring cancers. [29][30][31][32] However, the percentage of cases with AR mutations is probably lower and more on the order of o10% when all cases are taken into account. The majority of mutations reported map to the LBD.…”
Section: Amplification Of the Armentioning
confidence: 99%
“…Similar mutations in the same region have been reported. 29,30,[39][40][41] The type of treatment given was also shown to influence the kind of mutation seen. 42 Since reports have shown that mutations are present in 20-40% of the advanced PCAs before therapy, 30,31 it could be hypothesized that the mutations were not induced by therapy but were pre-existent.…”
Section: Amplification Of the Armentioning
confidence: 99%
See 1 more Smart Citation
“…1 Although such 'total androgen blockage' can induce tumor regression, the effect is often short-lived. It has been suggested that genetic changes of the androgen receptor (AR) may contribute to a poor response to hormone therapy; 2,3 however, the mechanisms responsible for androgenindependence remain uncharacterized.…”
mentioning
confidence: 99%